2015
DOI: 10.1007/s00468-015-1274-4
|View full text |Cite
|
Sign up to set email alerts
|

Responses to heatwaves of gas exchange, chlorophyll fluorescence and antioxidants ascorbic acid and glutathione in congeneric pairs of Acacia and Eucalyptus species from relatively cooler and warmer climates

Abstract: Two species from warmer climates, but not the corresponding congeneric species from relatively cooler ones, decreased stomatal conductance upon heatwaves, and one of them showed significant decrease in the efficiency of open reaction centres of PSII in the light. In contrast, responses of major antioxidants ascorbic acid and glutathione to heatwaves were more similar between congeneric species than between species from similar climates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Therefore, despite growing side‐by‐side with adequate water supply, species differed in stomatal regulation of T leaf during the heatwave, causing species to experience “different” heatwaves. Our results add to the growing number of studies showing that species may vary in their stomatal responses to high temperatures (Ameye et al, ; Drake et al, ; Fauset et al, ; Hammerlynck & Knapp, ; Urban et al, ; Wujeska‐Klause et al, ). Our results suggest that further work is required to identify patterns in stomatal responses to heatwave conditions across species, and associations with species performance during heatwaves.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Therefore, despite growing side‐by‐side with adequate water supply, species differed in stomatal regulation of T leaf during the heatwave, causing species to experience “different” heatwaves. Our results add to the growing number of studies showing that species may vary in their stomatal responses to high temperatures (Ameye et al, ; Drake et al, ; Fauset et al, ; Hammerlynck & Knapp, ; Urban et al, ; Wujeska‐Klause et al, ). Our results suggest that further work is required to identify patterns in stomatal responses to heatwave conditions across species, and associations with species performance during heatwaves.…”
Section: Discussionsupporting
confidence: 71%
“…heatwaves. Our results add to the growing number of studies showing that species may vary in their stomatal responses to high temperatures (Ameye et al, 2012;Drake et al, 2018;Fauset et al, 2018;Hammerlynck & Knapp, 1996;Urban et al, 2017;Wujeska-Klause et al, 2015). Our results suggest that further work is required to identify patterns in stomatal responses to heatwave conditions across species, and associations with species performance during heatwaves.…”
Section: Physiological and Biochemical Factors Associated With Specsupporting
confidence: 56%
See 1 more Smart Citation
“…In particular, extreme climate events and rapid changes in climate can cause physiological stress and damage to plants ( Bastos et al , 2014 ; Zinta et al , 2014 ). Threatened plant species are already in danger and thus are vulnerable to extreme climate events like the 2003 summer heatwave, showing that inappropriate land management can threaten the existence of plant species ( Bastos et al , 2014 ; Zinta et al , 2014 ; Wujeska-Klause, Bossinger & Tausz , 2015 ). Furthermore, we found that the threatened tree species within nature reserves would be strongly affected by climate change, particularly under the high concentration scenario by the 2080s.…”
Section: Discussionmentioning
confidence: 99%
“…Plant responses to high temperature, in addition to the damage triggered by this stress, vary widely among species and functional groups (Klockmann, Günter, & Fischer, ; Marias, Meinzer, & Still, ; O'Sullivan et al, ; Slot & Winter, ; Teskey et al, ; Wujeska‐Klause, Bossinger, & Tausz, ). Accordingly, the susceptibility of a plant to extremely high temperatures, a situation commonly observed during heat waves, appears to depend on a series of characteristics and adjustments at morpho‐anatomical (crown architecture, leaf size, and shape), physiological (transpiration rate and maximum stomatal conductance), and molecular (production of heat shock proteins, low‐weight compounds, and activation of the antioxidative defense system) levels (Bita & Gerats, ; Galmés, Kapralov, Copolovici, Hermida‐Carrera, & Niinemets, ; Griffin & Prager, ; Obata et al, ; Scafaro et al, ; Slot & Winter, ; Teskey et al, ; Wujeska‐Klause et al, ; Zhang et al, ). Moreover, the vulnerability of a species to high temperatures also depends on its growth strategy.…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 99%